The reliability and factor structure of Thai Young Schema Questionnaire-Short Form 3 - Chaiyun Sakulsriprasert (2018)
© 2016 Previous research which documented the psychometric properties of Young Schema Questionnaire (YSQ) was conducted in Western countries. The current research examined the reliability and factor structure of the Thai version of the Young Schema-Short From-3 (YSQ-S3). The participants were 622 undergraduates (62% females) recruited from three universities in Chiang Mai, Thailand. Results suggested acceptable internal consistency of 18 early maladaptive schemas (EMSs) (Cronbach's α range from 0.619 to 0.846). Confirmatory factor analysis confirmed the factor structures of 18 EMSs. The results failed to support Young's theoretical schema domain. The authors indicated a four-factor solution as the best alternative second-order model for this population. In conclusion, the Thai version of YSQ-S3 is psychometrically sound questionnaire that can be utilized for assessing EMS, both for research and practice purposes. The current study further provides evidence supporting the existence of 18 EMSs in the non-Western context.